A Neuropsychoanalytic Perspective. Issue 8 (17th November 2019) - Solms, Mark
ABSTRACT: The term 'neuropsychoanalysis' was introduced in 1999, but a concerted effort to integrate the findings of neuroscience with those of psychoanalysis began in 1986. The following is a commentary on the five essays published in this special issue, from the viewpoint of someone who worked under this banner from the outset. Alongside Antonio Damasio, whose work is well represented in the five essays, the commentator's closest collaborator since 1998 was the late Jaak Panksepp. The commentary adds more detail about Panksepp's important contributions to the topic of this special issue. It will be seen that, although Solms, Damasio, and Panksepp agree on the foundational issues at stake here, they do not agree on everything.